Effect of the subdose of human chorionic gonadotropin applied in the Hou Hai acupoint on ovulation induction in mares - Ribeiro, M. O.; Silva, M. A. A.; Maggitti Junior, L. D. P.; Bezerra, P. A.; Bittencourt, R. F.; Feliciano, M. A. R.; Santana, A. L. A.; Silva, P. D. A. [UNESP]; Barbosa, L. P. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
The objective of this study was to evaluate the effects of an hCG sub dose applied at the Hou Hai acupoint on corpus luteum (CL) quality and ovulation induction in mares. Fifteen crossbred mares were distributed in randomized blocks and used in three periods with each period employed as the blocking factor in three treatments: T1 = 1500 IU of hCG via intravenous (IV); T2 = 450 IU of hCG applied at the false acupoint (IV); and T3 = 450 IU of hCG applied at the Hou Hai acupoint. Mean diameter of the CL, serum concentration of progesterone (P-4), vascularization of the pre-ovulatory follicle and CL were evaluated. Females administered 450 IU of hCG at the Hou Hai acupoint exhibited greater ovulation rates (33.33%) 48h after induction; The minimum number of colored pixel (NCP) of the pre-ovulatory follicle of control females was superior (40.33) to that of mares administered 450 IU of hCG IV at the false acupoint (36.84) and similar to that of those administered hCG at the Hou Hai acupoint (39.31). Further, moderately positive correlations were found between the CL diameter and the P-4 concentration on D8 (P<0.05). IV administration of 450 IU of hCG or at the Hou Hai acupoint was efficient at inducing ovulation and ensuring the quality of CL in mares.
Keywords: Doppler; equine; pharmacopuncture; hormone therapy; progesterone